Climate shifts vs. edaphic humidity and the difficulty of palaeoreconstructions – a malacological study on stable isotopes in Quaternary dune sequences of Fuerteventura. (25th March 2021) - Richter, Christiane; Roettig, Christopher‐Bastian; Wolf, Daniel; Gärtner, Andreas; Kolb, Thomas; Faust, Dominik
ABSTRACT: Dune palaeosurface sequences on the Eastern Canary Islands were investigated for stable isotope records in gastropod shells of the genus Theba . Due to the ecology of the taxon and the special oceanic insularity of the study site, we assume that δ 18 Oshell signals in our case mainly reflect shifts in δ 18 O signals of sea surface water. We found that a rapid decrease in δ 18 Oshell signals is associated with significant changes in gastropod associations. We suggest that these faunal changes were caused by strong (hot) winds at the end of glacial phases, that were described previously by Moreno et al . In addition, we assume that rapid declines in δ 18 Oshell signals due to marine transgressions were followed by geomorphologically stable phases, dominated by dust enrichment. Such palaeosurfaces correlate with maxima of gastropod biodiversity and with more negative δ 13 Cshell signals indicating a higher proportion of C3 plants. Based on our results, we also assume that these silty palaeosurfaces were associated with increased soil moisture conditions due to a higher water storage capacity of the finer substrate, independent of climatic moisture conditions.